2019
DOI: 10.3390/ijms20102504
|View full text |Cite
|
Sign up to set email alerts
|

MST1 Regulates Neuronal Cell Death via JNK/Casp3 Signaling Pathway in HFD Mouse Brain and HT22 Cells

Abstract: Oxidative stress has been considered as the main mediator in neurodegenerative diseases. A high-fat diet (HFD) and metabolic diseases result in oxidative stress generation, leading to various neurodegenerative diseases via molecular mechanisms that remain largely unknown. Protein kinases play an important role in the homeostasis between cell survival and cell apoptosis. The mammalian sterile 20-like kinase-1 (MST1) protein kinase plays an important role in cellular apoptosis in different organ systems, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…ROS assay was performed as previously described with slight modification [38,39]. The cells were cultured in 96-well plates in 200 μL DMEM containing 10% FBS and 1% penicillin/streptomycin in every well.…”
Section: Methodsmentioning
confidence: 99%
“…ROS assay was performed as previously described with slight modification [38,39]. The cells were cultured in 96-well plates in 200 μL DMEM containing 10% FBS and 1% penicillin/streptomycin in every well.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that consumption of a high-calorie diet intake enhanced oxidative stress in several tissues, including brain tissue [34,49]. Similarly, others also demonstrated that consumption of HFD significantly reduced the protein expression level of hemeoxygenase-1 (HO-1) and nuclear factor-2 erythroid-2 (Nrf-2) in HFD-fed mice brains [28].…”
Section: Hfd Induces Oxidative-stress-mediated Brain Insulin Resistanmentioning
confidence: 97%
“…Activation of the MST1-JNK pathway has been described to promote cell death (72). We, thus, studied whether chronic GPER1 actions deactivate the MST1-JNK axis in H9c2 cardiomyoblasts treated with H 2 O 2 agent.…”
Section: Chronic Gper1 Activation Reduces Mst1-jnk Signalingmentioning
confidence: 99%